Virtual educational nutrition workshops for people with mental suffering in the context of COVID-19: an experience report (Research, Society and Development, 2021)
With the pandemic context, due to COVID 19, social distancing became essential as a form of prevention, making it necessary for research and extension actions to reinvent themselves. The work in question aims to report the experience of the Nutrition Education for People with Mental Distress project working at the Living and Cultural Center, during 2020, in the context of the COVID-19 pandemic. This is a descriptive experience report. Initially, the approach took place through digital material in the form of flyers sent by the WhatsApp application to users. With the need for greater proximity, animated educational videos were produced, sent to users who were interested in participating in the actions. From March 2020 to March 2021, eight flyers were produced with themes focused on prevention and care against COVID-19 and nineteen videos with themes focused on nutrition and health. The interaction with users, even if digitally, allowed the continuity of social interaction, so important for the population in question, as well as the transfer of knowledge and truthful information. However, the possibility of resuming face-to-face workshops is not highlighted, as they allow better communication and user engagement.